The temptation to exist - Cioran, Emile Michel, 1911-1995; Howard, Richard, 1929-2022; Sontag, Susan, 1933-2004 (Chicago : University of Chicago Press, 1998)
Cioran denkt in dit boek na over de vraag "Wat maakt het leven waard geleefd te worden?".
Originally published: New York : Seaver Books : Distributed by H. Holt, 1986, c1968.